2022
DOI: 10.1007/s11356-021-18224-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of green lending on credit risk: evidence from UAE’s banks

Abstract: This study investigates the impact of UAE’s Green Credit Policy on the non-performing loan. One of the main pillars in the UAE green agenda 2015–2030 is the green finance that has been growing in high acceleration in the Gulf Cooperation Council (GCC) countries and the whole world. Consequently, the main objective of this study is to investigate in the financial risks that associated with green lending and whether an increasing in green lending will decrease the non-performing loans ratio (NPLR) of UAE banks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…The next generation of money is the fiat money, which does not require the backing of a physical commodity [ 6 ]. Instead, the value of fiat currencies is set by supply and demand and people's faith in its worth.…”
Section: Discussion and Conclusion Drawn From The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The next generation of money is the fiat money, which does not require the backing of a physical commodity [ 6 ]. Instead, the value of fiat currencies is set by supply and demand and people's faith in its worth.…”
Section: Discussion and Conclusion Drawn From The Studymentioning
confidence: 99%
“…The good news is that the new technology has made the first steps toward transformation much easier than they were just a few years ago. From gathering the data to orchestrating and optimizing campaigns, every step on the banks’ path to digital transformation has been further simplified by modern AI-driven tools [ 6 , 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data mining (DM), which is a fundamental technology that supports BIA, uses a quantitative data analysis tool to identify patterns and rules in data resources and find logical relationships that summarize data in a new, understandable, and useful way to support organizational business intelligence and management decisions [19][20][21]. A key value of data mining in business intelligence and analytics is to anticipate a particular behavior or outcome based on data models, in what is known as predictive analytics, thus giving the most likely outcome leading to better management decisions and future planning [6,22].…”
Section: Business Intelligence and Analytics (Bia)mentioning
confidence: 99%
“…Commercial banks can cope with green credit shock through risk control. Al-Qudah et al [33] demonstrated that the green loan ratio hurts the NPL ratio and equity returns. Del et al [34] found that banks with high green loan weights have lower credit and default risk and lower profitability.…”
Section: Theoretical Backgroundmentioning
confidence: 99%